A metal tolerance protein, MTP10, is required for the calcium and magnesium homeostasis in Arabidopsis. (31st December 2022) - Ge, Haiman; Shao, Qiaolin; Chen, Jinlin; Chen, Jiahong; Li, Xueqin; Tan, Yu; Lan, Wenzhi; Yang, Lei; Wang, Yuan
ABSTRACT: Nutrient antagonism typically refers to the fact that too high a concentration of one nutrient inhibits the absorption of another nutrient. In plants, Ca 2+ (Calcium) and Mg 2+ (Magnesium) are the two most abundant divalent cations, which are known to have antagonistic interactions. Hence, maintaining their homeostasis is crucial for plant growth and development. In this study, we showed that MTP10 (Metal Tolerance Protein 10) is an important regulator for maintaining homeostasis of Mg and Ca in Arabidopsis. The mtp10 mutant displayed severe growth retardation in the presence of excess Mg 2+, to which the addition of Ca 2+ was able to rescue the phenotype of mtp10 mutant. Additionally, the deficiency of Ca 2+ in the culture medium accelerated the high-Mg sensitivity of the mtp10 mutant. The yeast complementation assay suggested that AtMTP10 had no Ca 2+ transport activity. And the ICP-MS data further confirmed the antagonistic relationship between Ca 2+ and Mg 2+, with the addition of Ca 2+ reducing the excessive accumulation of Mg 2+ and high-Mg inhibiting the uptake of Ca 2+ . We conclude that the Arabidopsis MTP10 is essential for the regulation of Mg and Ca homeostasis.